PEMBENTUKAN KARAKTER MANDIRI PADA ANAK USIA DINI MELALUI METODE MONTESSORI DI TK ALMARHAMAH CIMAHI - Cucu Sunarti; Wiwin Uwie; Agus Sumitra (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
This journal was to give knowledge for early childhood tutors about learning strategies to improve the emotion social of children abilities. When the learning strategy used by an early childhood tutors was effective, so the achievement level of emotional social intelligence will be maximized and child will grow into a child of character. Character is the key of individual success. It means that someone activity an life wants to succeed, so the absolute requirement must be supported by a strong character capacity. The high character qualities of the community will foster a strong desire to improve the nation quality. In early childhood emotional social development, several assessment reference of early childhood tutor will find it easier to assess and measure the emotional social of children abilities. Learning strategies that are not commonly known by early childhood tutors are learning strategies with Montessori method. Learning with Montessori methode caracter development designed the freedom to think, work and do something.